(untitled) (Research, Society and Development, 2022)
The objective of this article was to review the historical milestones of the Brazilian hydroelectric sector since its birth, at the end of the 19th century, until the year 2021. This period was divided into five phases, characterized according to the political and economic, national and international that shaped the Brazilian hydroelectric sector. Adopting the bibliographic method, the research corpus consists of reports and books produced by the government; official statistical databases published by regulatory bodies and energy companies; scientific works (articles, dissertations and books), and; applicable governing laws. From this narrative review, it was inferred that: 1) The big hydroelectric plants played a leading role, in terms of infrastructure, in all national developmental projects that rose to power in Brazil since the 1930 revolution; 2) Events such as the New York Stock Exchange crash in 1929 and the Second World War show how susceptible the Brazilian hydroelectric sector is to the nuances of international geopolitics; 3) The energy insecurity scenarios cannot be explained only by the various water crises that devastated the country in the analyzed period, and; 4) The “2001 blackout crisis” is the main catalyst in the history of the Brazilian electricity sector: It triggered both the execution of the last cycle of hydroelectric projects of great magnitude in Brazil and the diversification of the national energy matrix, primacy of the regulatory efforts underway since the beginning of this century.